The relationship between dietary micronutrients and endometriosis: A case-control study - Ghazal Roshanzadeh; Shahideh Jahanian Sadatmahalleh; Ashraf Moini; Azadeh Mottaghi; Farahnaz Rostami (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Fewer studies were on micronutrient intake in women with endometriosis, and the etiology of endometriosis remains unclear between dietary micronutrients and the risk of endometriosis. Objective: This study aimed to investigate the relationship between dietary micronutrients and the risk of endometriosis. Materials and Methods: This case-control study was conducted on 156 women (18-45 yr) with and without endometriosis in the gynecology clinic of Arash hospital between May 2017 and May 2018 in Tehran, Iran. According to the laparoscopic findings, the participants were divided into 2 groups (n = 78/each), women with pelvic endometriosis as the case group and women without endometriosis pelvic as the control group. Dietary data were collected using a validated 168-item semiquantitative food frequency questionnaire with the standard serving. A logistic regression model was used to determine the association between micronutrients and the risk of endometriosis. Results: Data analysis showed a significant relationship between micronutrients such as: potassium (OR: 0.74; CI: 0.56-0.99; p = 0.01), calcium (OR: 0.70; CI: 0.52-0.94; p = 0.003), and also among the vitamin C (OR: 0.70; CI: 0.52-0.94; p = 0.02), B2 (OR: 0.73; CI: 0.55-0.98; p = 0.01), and B12 (OR: 0.71; CI: 0.53-0.95; p = 0.02) with endometriosis, so those who used fewer micronutrients were at higher risk of endometriosis. Conclusion: The findings showed that the dietary intakes of calcium, potassium, vitamins B12, B2, B6, and C are inversely related to the risk of endometriosis.